The Analysis of Risk and Return Comparation Between Silver, Gold, JKSE, and Property in Pasar Kemis, Sukamantri, Kutajay, Gelam Jaya and Kutabaru Wards in Kabupaten Tangerang for Long Term Investment - Putri, Lupita; Soekarno, Subiakto (Journal of Business and Management, 2012)
Nowadays, investment term has become a common word be heard and be talk of many people, from businessmen to students, even among the housewives. The understanding that the investment of capital or funds are placed in assets which are expected to provide benefits or the value will rise someday in the foreseeable future, it means investing is done by 'sacrificing' the potential of current consumption to get better opportunities or greater in the future. Generally, the purpose of investment is to fulfill the needs and desires in order to improve the quality of life. In order to achieve those needs and desires, then the investment is one of the best solution. Indonesia's strong economic growth and favorable demographics make it a great country for investors, but there are several risks that investors should be aware of before committing any capital. There are several benefits of investing in Indonesia, Indonesia has strong historic growth. Indonesia has been one of the best performing investments throughout the world economic crisis that began in 2008. The types of investment instrument is quite widely and variously. It could be real or paper investment, such as stocks, bonds, mutual funds, precious metals, property, and even open your own real business. In this term, author will analyze risk and return of silver, gold, JKSE, and Pasar Kemis, Sukamantri, Kuta Jaya, Gelam Jaya, Kuta Baru Property in KPP Kosambi, Tangerang. Methodology used in this research are Problem Identification, Theoretical Foundation, Data Collection, Data Analysis, and the last step is Conclusion and Recommendation. These steps need to be conducted in order to complete the project. Basically, the writer want to analyze the risk and return and give the result to determine the highest return of instrument investment the recommendation for retirement financial purposes. Correlation must be analyzed also for the recommendation for the choices of investment proportion. The Conclusion came out with Pasar Kemis property as the best investment instrument with the highest point in Treynor in risk adjusted method. The combination of two investment which came out with the best correlation is Pasar Kemis property and Silver. These two investments give the most negative result which means that the movement towards market would be in contrast to each other and give the best diversified portfolio. Further research is could be the recommendation in order to construct an optimal portfolio investment.Key Words : Investment Instruments, Risk and Return, Silver, Gold, JKSE, Property